Childhood‐onset schizophrenia case with 2.2 Mb deletion at chromosome 3p12.2–p12.1 and two large chromosomal abnormalities at 16q22.3–q24.3 and Xq23–q28. Issue 4 (2nd February 2015) - Rudd, Danielle; Axelsen, Michael; Epping, Eric A.; Andreasen, Nancy; Wassink, Thomas
Key Clinical Message Childhood‐onset schizophrenia is rare, comprising 1% of known schizophrenia cases. Here, we report a patient with childhood‐onset schizophrenia who has three large chromosomal abnormalities: an inherited 2.2 Mb deletion of chromosome 3p12.2–p12.1, a de novo 16.7 Mb duplication of 16q22.3–24.3, and a de novo 43 Mb deletion of Xq23–q28.